2019
DOI: 10.1108/ijem-11-2017-0320
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing abusive school leadership practices through the lens of social justice

Abstract: Purpose The present study contributes to the growing body of research on abusive supervision in school settings, particularly by principals. School leadership (principal) behavior has been a topical issue for decades in educational research. This paper attempts to add to scholarly knowledge in the area of school leadership and specifically the effect of abusive school leadership on organizational productivity and organization citizen behavior. Put succinctly, the purpose of this paper is to examine the implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
4
0
1
Order By: Relevance
“…Therefore, it is reasonable to assume that abusive leadership harms school teachers' motivation as well. This is consistent with claims that abusive school leadership has a negative influence on teachers' performance, productivity, turnover, well-being, and health (Khumalo, 2019, 2021). In one of the rare studies about the effect of abusive school leadership on American teachers, it was found that half of the teachers experienced fear, depression, low self-esteem, and a decrease in work motivation (Blase et al.…”
Section: Theoretical Backgroundsupporting
confidence: 90%
“…Therefore, it is reasonable to assume that abusive leadership harms school teachers' motivation as well. This is consistent with claims that abusive school leadership has a negative influence on teachers' performance, productivity, turnover, well-being, and health (Khumalo, 2019, 2021). In one of the rare studies about the effect of abusive school leadership on American teachers, it was found that half of the teachers experienced fear, depression, low self-esteem, and a decrease in work motivation (Blase et al.…”
Section: Theoretical Backgroundsupporting
confidence: 90%
“…People who work in the education sector tend to be motivated by both material rewards and an intrinsic desire to make a positive difference for students or society (Ahluwalia and Preet, 2019; Imran et al , 2017), so studying the influence of their materialism and idealism on their responses to career-related frustrations is highly pertinent. Moreover, abilities to shield themselves from destructive leadership styles and have a say in organizational decision making are two important features that employees in this education sector tend to seek and value (Khumalo, 2019; Oplatka and Stundi, 2011), so exposures to abusive supervision and experiences of decision autonomy may have notable influences on their reactions to their beliefs that they have had to make compromises in their careers. From a more general perspective, by focusing on one industry sector, I diminish the chances that pertinent industry characteristics influence the tested relationships, such as the supply and demand of valuable employees or the costs associated with the decision to leave an organization (Amankwaa and Anku-Tsede, 2015; Joo et al , 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Abusive supervision does have ramifications on the individual, school as an organization, the family of the abused individual, the health of the abused and the education system. (Khumalo, 2019). The effect on the victim is that not only his/her health is affected but also suffers emotionally and their well-being is greatly affected (Duffy, Ganster, & Pagon, 2002;Hobbler & Brass, 2006).…”
Section: Harmful Consequences Of Abusive School Leadershipmentioning
confidence: 99%